Genomic Surveillance Detection of SARS-CoV-1–Like Viruses in Rhinolophidae Bats, Bandarban Region, Bangladesh - Christopher Bradburne; Ausraful Islam; Ian Bird; Elliott Abbott; Sarah Harrison; Morgan Chunn; Diana Radune; Md Rakib Hasan; Brian Janes; Sean Lovett; John Lagergren; Timothy O’Hanlon; et al. (Emerging Infectious Diseases, 2025)
We sequenced sarbecovirus from Rhinolophus spp. bats in Bandarban District, Bangladesh, in a genomic surveillance campaign during 2022–2023. Sequences shared identity with SARS-CoV-1 Tor2, which caused an outbreak of human illnesses in 2003. Describing the genetic diversity and zoonotic potential of reservoir pathogens can aid in identifying sources of future spillovers.